Pengaruh Gaya Kepemimpinan, Budaya Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Hania Natura Indonesia - Waluyo Waluyo; Rakhmat Rakhmat; Irdawati Irdawati; Asrul Asrul (Al-Buhuts, 2025)
This study investigates the influence of leadership style, work culture, and job satisfaction on employee performance at PT Hania Natura Indonesia. A quantitative approach with a survey design was employed, involving 36 respondents selected using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that leadership style does not have a significant impact on employee performance, whereas work culture and job satisfaction exert a significant positive effect. Furthermore, the three variables collectively have a significant influence on employee performance. These results highlight that employee performance improvement is more strongly driven by a supportive work culture and high levels of job satisfaction, while leadership style requires further development to enhance its contribution. The practical implication of this research suggests that management should prioritize strategies to strengthen organizational culture and improve job satisfaction, while simultaneously refining leadership practices to ensure sustainable employee performance and organizational growth.